Development of Pencak Silat Collaboration Test Instruments for Pencak Silat Athletes in Jambi City - Putra, Muhamar Kodafi (PPSDP International Journal of Education, 2023)
In this research journal, the writer or researcher wants to conduct research on the Development of a Pencak Silat Punch and Kick Collaborative Test Instrument for Pencak Silat Athletes in the City of Jambi. The method used in this research is research and development. The sample used was 16 pencak silat athletes in Jambi City. The results of the study “Development of a Pencak Silat Punch and Kick Collaborative Test Instrument for Jambi City Athletes” were categorized as suitable as a punch and kick collaboration test instrument that could measure the speed and strength of each the punches and kicks of Jambi City’s pencak silat athletes. This can be seen from the results of the assessment of media experts, namely 91.88%, test and measurement experts 100.00%, and material experts in pencak silat 100.00% and based on the results of medium-scale trials, namely 96.30%.